Climatic factors influencing agriculture in the low rainfall tract of Bellary in Mysore State - RAMANATH, B.; RAO, D. HAYAVADANA; RAO, S. B. PRABHANJAN; VERMA, BALVIR (MAUSAM, 1973)
The general climatic features of Bellary based mainly on the data recorded at the Soil Conservation Research Farm for the period 1956.69 are presented. The short period rai11fall data of the farm is compared with 100-year rainfall record of the Bellary Observatory regarding amounts, distribution and monthly probabilities of occurrence of rain of specific amount.